70.8k views
1 vote
Condense the following logs into a single log:


5log_(b) x - 6log_(b) y

User Themean
by
5.8k points

2 Answers

3 votes

Answer:


5\log_b(x)-6\log_b(y)=\log_b((x^5)/(y^6))

Explanation:

The given logarithmic expression is
5\log_b(x)-6\log_b(y)

We apply the rule:
n\log_b(M)=\log_b(M^n)

This implies that;


5\log_b(x)-6\log_b(y)=\log_b(x^5)-\log_b(y^6)

We now apply the rule;
\log_a(M)-\log_a(N)=\log_a((M)/(N) )


5\log_b(x)-6\log_b(y)=\log_b((x^5)/(y^6))

User Thao
by
5.1k points
3 votes

Answer:


logb(X^5 / Y^6)

Explanation:

Given in the question an expression

5logbX - 6logbY

To Condense the following logs into a single log we will use logarithm rules

1) log power rule

5logbX = logbX^5

6logbY = logbY^6

2)log qoutient rule

ln(x/y) = ln(x)−ln(y)

logbX^5 - logbY^6 =
logb(X^5 / Y^6)

User Scottohara
by
5.6k points